Pengaruh Supervisi Akademik Kepala Sekolah dan Motivasi Kerja Guru Terhadap Kinerja Guru - Moulina, Dewi (Journal of Innovation in Teaching and Instructional Media, 2022)
This study aims to determine the effect of the principal's academic supervision and work motivation on teacher performance at SMA Negeri 10 Palembang. The research method used is using a quantitative research method approach with the number of samples used as many as 68 teachers. The research instrument in this study used a questionnaire for data collection and the IBM SPSS application for statistical data processing. Data analysis uses based on decisions made based on the results of data analysis to test predetermined hypotheses. The results obtained indicate that the principal's academic supervision and work motivation have a positive and significant effect on teacher performance simultaneously. The results of this study are expected to contribute as a reference or teacher evaluation in planning the learning process in the next semester.